OP0346 MRI OF THE WRIST IN EARLY RHEUMATOID ARTHRITIS AFTER 1-YEAR TREAT-TO-TARGET STRATEGY. (June 2019) - Fan, XIAO; Griffith, James F; Tam, Lai-Shan
Abstract : Background: There are two types of remission in rheumatoid arthritis. The first, and most commonly applied, is clinical remission. Imaging remission is another aspect to consider given that (a) the correlation between clinical and imaging at presentation is only modest, (b) imaging can show subclinical inflammation not evident clinically and (c) imaging evidence of inflammation can predict structural damage (1). In this study, we compared clinical and imaging remission in early rheumatoid arthritis (ERA) patients after one year of standard treatment. Objectives: To semi-quantitatively and quantitatively measure the degree of inflammation (synovitis, tenosynovitis, bone marrow oedema) and structural change (erosions, joint space narrowing) on MRI in early RA patients following treat-to-target strategy treatment for one year and to compare this with changes in clinical parameters. Methods: Prospective cross-sectional study of 70 ERA patients underwent treat-to-target strategy treatment for one year. DAS28-ESR remission (DAS28-ESR score ≤3.2), 2011 ACR/EULAR definition of remission, SDAI remission (SDAI ≤ 3.3) and Boolean remission was measured before and after treatment. High resolution MRI of the most symptomatic wrist was performed before and after treatment. MRI parameters including RAMRIS subscores, synovial volume (synovitis and tenosynovitis), synovial perfusion (max enhancement, enhancement slope) were measured. Results: 55 (%) out of 70 ERA patients completed baseline and one-year clinical and MRI assessments. Remission rates for DAS28-ESR, SDAI and Boolean were 60% (33), 44% (24) and 33% (18) respectively. Eight (24%) out of 33 patients with DAS28-ESR remission, showed progression in bone erosion. Four (16.7%) of 24 patients with SDAI remission showed progression in bone erosion while 1 (5%) of 18 patients with Boolean remission showed progression in bone erosion. Patients who achieved remission after treatment had a greater reduction in all MRI-evident inflammation as well as bone erosion. At month 12, MRI-evident joint synovitis, tenosynovitis and bone marrow oedema was still frequently seen in ERA patients with clinical remission though patients who achieved Boolean remission had the lowest levels of joint synovitis (RAMRIS Synovitis= 2.6±0.8 (2.9±1.3 for SDAI remission and 3±1.2 for DAS28-ESR remission); synovitis volume= 1298±1217 mm 3 (1480±1367 mm 3 for SDAI remission and 1520±1584 mm 3 for DAS28-ESR remission); synovitis perfusion of max enhancement= 38±22% (41±24% for SDAI remission and 41±25% for DAS28-ESR remission)), bone marrow oedema (RAMRIS BME score= 0.9±1.1 (1.3±2.6 for SDAI remission and 1.4±2.3 for DAS28-ESR remission)) as well as bone erosion (RAMRIS bone erosion score= 4±5.8 (4.6±5.5 for SDAI remission and 4.3±4.9 for DAS28-ESR remission)) for all patients at one year. Conclusion: MRI detected inflammation is common even in patients with clinical remission. Patients with Boolean remission had overall less residual inflammation than DAS28-ESR or SDAI remission patients as well as lowest number of patients who had bone erosion progression in remission group at month 12. Treat to target protocols should ideally target Boolean remission. Reference: [1] Anandarajah A, Thiele R, Giampoli E et al. Patients with rheumatoid arthritis in clinical remission manifest persistent joint inflammation on histology and imaging studies. J Rheumatol. 2014 Nov;41(11):2153-60. Disclosure of Interests: None declared